FNAC of Hepatic Malignancy and it’s Clinical Correlation. - Manik, Abul Hayat; Ekram, Rezaul; Mallik, Pranab Kumar; Mahzabeen, Moushumi; Islam, Md. Rafikul; Amin, Md. Robed (Bangladesh Critical Care Journal, 2019)
Background: Hepatic malignancy is an important clinical condition which is associated with poor outcome. Clinicalassessment of a patient with hepatic malignancy is crucial to sort out the primary and secondary, and so biochemicaland radiological investigations are needed. Hence fine needle aspiration cytology (FNAC) of the lesion is essentialwhich is a minimal invasive procedure to combat a deadly disease. Objective: The aim of this prospective cross sectional observational study was clinical assessment of primary andsecondary hepatic malignancy and its co-relation with FNAC of hepatic malignancy. Methods: Patients admitted in Medicine Department, Dhaka medical College, with hepatic malignancy from January2013 to June 2014 and then confirmed by FNAC (USG guided) of liver mass were included in the study. A total 100patients were enrolled in the study in a non-random convenient sampling method. Result: In this study 42 patients were found having primary Hepatocellular Carcinoma (HCC) and 58 patients hadsecondary hepatic malignancy. FNAC confirmed secondary hepatic malignancy (n=58) as metastatic adenocarcinoma43(74.1%), metastatic small cell carcinoma 9(15.5%), Gastro Intestinal Stromal Tumour (GIST) 2(3.4%), squamouscell carcinoma 2(3.4%) & Non Hodgkins lymphoma 2(3.4%). Most of the patients of primary hepatic malignancybetween 20-40 years 18(42.9%) and secondary hepatic malignancy between 40-60 years 35(60.3%). Incidence in maleis more in both primary 31(73.8%) and secondary 38(65.5%) hepatic malignancy. Both HCC and secondariespredominantly presents with abdominal pain, 39(92.9%) cases of HCC and 47(81.0%) of secondaries. Incidence ofmultiple lesion in ultrasonogram is more in both primary 30(71.4%) and secondary 47(81.0%) hepatic malignancy.Positive HBsAg, Positive Anti HBc (total), Positive Anti HCV were found in 15(35.7%), 11(26.2%) and 9(21.4%) casesof HCC respectively. Positive Alpha Feto Protein (AFP) was found insignificant in this study. Conclusion: Fine Needle Aspiration (FNA) is a useful diagnostic test for evaluating patients with discrete hepaticmasses. Correlation with clinical, radiological and cytological findings is helpful in arriving at the correct diagnosisand therefore increases overall accuracy and cost-effectiveness of the procedure. Bangladesh Crit Care J September 2019; 7(2): 81-85